History-Based Image Cloud Recognition Learning Method in Strengthening Students' Historical Thinking Skills - Amin, Syaiful; Sariyatun, Sariyatun; Gunarhadi, Gunarhadi; Purwanta, Purwanta (Journal of Nonformal Education, 2024)
ch school that is the subject of research are adequate and complete to support the learning process, although there are some that still need care. The history learning media used by history teachers is still in the form of presentation media that collaborates with static images or text, making it less interesting and monotonous. Public History-based Image Cloud Recognition learning media designed to be developed by applying android applications, cloud storage, and camera scans to scan content from images of historical objects. The results of the material expert validation test obtained an average score of 4.39 and the media expert validation test obtained an average value of 4.45 so that both values were included in the "Very Good" category. Meanwhile, based on trials to students in small groups, an average score of 4.61 was obtained; In the limited group, a value of 4.28 was obtained and in the broad group, an average value of 4.58 was obtained. All three grades are classified as "Very Good". The effectiveness of products designed according to the results of the t test (t count > t table) is known that Public History based Image Cloud Recognition learning media is effective in improving students' historical thinking skills and making learning more interesting, active, and dynamic.